(3fXQjGJ GdEYdGe hGdEJUGd (B: s (3GdSfI GdKGdKI GJUGd (B/ s - (3YRhR, SYjOIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2018)
(3JMOjO HYV GdeaGgje GdGhdjI h fTCI fXQjGJ GdGYdGe h GdGJUGd h JCKjQGJ hSGFd GdGJUGd (B.s
(3eQGLY U(B.103s
Keywords: (3GdGJUGds; (3GdGYdGes